Socialization of the Implementation of Sharia Contracts in the Management of UP2K as an Effort to Increase Islamic Economic Literacy in the Community - Budi Santoso, Muhammad Syafi'i; Nasiruddin, Muhammad; Habibi, Rakhmawan; Hidayati, Nur Laily; Al Azhar, M Farid; Syahni, Ahmad; M. Umar Ahfadz (Edumedia Solution, 2025)
This community service activity aims to improve Islamic economic literacy through the socialization of the implementation of sharia contracts in the management of Family Income Improvement Enterprises (UP2K). The activities were carried out in the form of interactive lectures, group discussions, and simple training based on case studies. The target group of the activity was the UP2K management group and the surrounding community actively involved in productive economic activities. The results of the activity showed an increase in participants' understanding of the basic concepts of sharia contracts and an awareness of the importance of applying these principles in daily economic activities. Participants also expressed interest in developing Sharia-based UP2K more systematically in the future. Thus, this activity is expected to be the first step in encouraging the transformation of the community economy towards a system that is fairer, more transparent, and in accordance with Islamic values